Aortic Dissection in the Young: A Case Report and Review of the Differential Diagnostic Considerations. Issue 1 (March 2013) - Lynch, David; Hughes, Rhome
Aortic dissection is a rare cause of death in young adults, which may be caused by acquired or congenital factors. We present the case of a 21-year-old man who died as a result of spontaneous aortic dissection and cardiac tamponade. At autopsy, signs of Marfan syndrome were evident both grossly and microscopically. Hodgkin lymphoma was also discovered, though was noncontributory to death. We review the causes of aortic dissection in young individuals, with a focus on the key differentiating features of predisposing inheritable connective tissue disorders. Given the implications for surviving family members, it is the obligation of the diligent forensic pathologist to be aware of these conditions, such that families may be alerted to the need for genetic counseling.